Pulse oximetry as a simple diagnostic test for persistent pulmonary hypertension of newborn in limited resource settings - Shirly Anitha, G. Fatima; Lakshmi, S.; Darlington, C. Danny (International Journal of Contemporary Pediatrics, 2016)
Background: Persistent Pulmonary Hypertension of newborn (PPHN), results from the disruption in the normal perinatal fetal- neonatal circulatory transition. The condition remains a difficult neonatal emergency to manage which is mainly attributed to the delay in diagnosis and stabilisation. Although the management of PPHN involves advanced diagnostic and therapeutic interventions, our study highlights that PPHN can be diagnosed even in limited resource settings, with simple bedside evaluation of pre-ductal and post-ductal saturation (Spo2) difference. Methods: A retrospective study of neonates with PPHN, admitted in NICU, of a government hospital in a limited resource setting, over a period of 6 months. Results: Out of the 592 neonates admitted during the 6 months period in NICU, PPHN was diagnosed in 26 neonates (4.4%).The incidence was higher for male (57.7%),term gestation (84.6%), and appropriate for gestational age- AGA (88.5%). Meconium aspiration (53.8%) followed by perinatal asphyxia- clear liquor (30.8%) were the most common underlying etiology for PPHN in our study. Around 61.5% were diagnosed with PPHN based on pulse oximetry alone before the first dose of sildenafil, which was confirmed by ECHO later in 75% of the cases. PPHN improved in 92.3% of the study population (24/26 cases), out of which 62.5% were diagnosed based on pulse oximetry alone before intervention. Conclusions: Our study emphasises that even in peripheral health centres with limited resources, PPHN can be diagnosed by pulse oximetry (pre and post ductal Spo2 difference of >10%) along with clinical assessment. Such critically ill neonates can be initiated on pulmonary vasodilators like sildenafil and stabilised at the earliest that is crucial before referral to a tertiary care centre.